Problems and Comparisons Regarding The Implementation of Marriage Laws Towards The Dissemination of Islamic Law Compilations - Muhammadong, Muhammadong; Khaerunnisa, Khaerunnisa; Muthmainnah, Sitti; Nurhilaliyah , Nurhilaliyah (MSJ : Majority Science Journal, 2024)
This research aims to identify problems in the implementation of Law Number 1 of 1974 concerning Marriage related to Presidential Instruction Number 1 of 1991 which regulates the dissemination of the Compilation of Islamic Law as a juridical basis. Although the Marriage Act of 1974 regulates various aspects of marriage in general, it does not explicitly regulate, legalize, or prohibit interfaith marriage. This raises the need for further elaboration in order to cover all religions regulated by the state. The birth of Presidential Instruction No. 1 of 1991, which aims to disseminate the Compilation of Islamic Law, faces challenges in implementation due to its lower position in the legal hierarchy compared to the Marriage Law. Therefore, even though this Presidential Instruction provides additional guidance, marriage issues must still refer to higher and more general rules. This research will explore how the integration of these two regulations can be done to create a consistent and fair legal system.